A simple fluorescence based assay for quantification of human immunodeficiency virus particle release - Hermle, Johannes; Anders-Ößwein, Maria; Heuser, Anke-Mareil; Müller, Barbara (BMC biotechnology, 2010)
The assembly and release of human immunodeficiency virus (HIV) particles from infected cells represent attractive, but not yet exploited targets for antiretroviral therapy. The availability of simple methods to measure the efficiency of these replication steps in tissue culture would facilitate the identification of host factors essential for these processes as well as the screening for lead compounds acting as specific inhibitors of particle formation. We describe here the development of a rapid cell based assay for quantification of human immunodeficiency virus type 1 (HIV-1) particle assembly and/or release.
Gesehen am 26.04.2023